The Relationship of Teacher Perceptions about Principal’s Leadership and Work Motivation with Teacher Performance - Nofrial, Nofi; Syah, Nurhasan; Purwanto, Wawan (LPPM Undiksha, 2019)
The aim to reveal and describe: Firstly The relationship between teachers' perceptions about principal's leadership with teacher performance, Secondly The relationship between work motivation and the teacher performance, Lastly The relationship between teachers' perceptions about the principals' leadership and work motivation together with the performance. This research uses a quantitative method that is correlational, the population in this research was as many as 73 teachers of SMK N 2 Sungai Penuh. The sampling technique in this research uses random sampling. Data collection techniques using instruments in the form of a questionnaire. The data analysis technique was carried out using the correlational technique with the help of the SPSS 21 application to determine the relationship between variables both individually and together, and the results of the study show: Firstly there is a significant relationship between teachers' perceptions of school principal's leadership and teacher performance, Secondly there is a significant relationship between work motivation and teacher performance, Lastly there is a significant relationship between teachers' perceptions about the principal's leadership, and work motivation together with teacher performance.